(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The linguistic culture in our Arab world has not experienced the same level of development and acceptance as it has in the Western world. Arab linguists attribute this to several factors that hinder its progression. One of these factors is the attitude of those engaged in Arabic studies in general, and Arabic grammar in particular, toward linguistic studies that follow the linguistic orientation. They see this approach as biased and dismissive, attributing it to the fact that most researchers in the Arabic language are traditionalists who cling to the old and find it difficult to accept modernity. However, this research argues that the rift between the two fields has deeper, more objective reasons. These include certain principles upon which linguistics bases its studies, aspects specific to some Arab linguistic studies, and factors related to the Arab researcher’s linguistic heritage and knowledge base. Overall, this research seeks to identify the issues that separate Arabic grammar from linguistics, as seen by a scholar of grammar, with the aim of building bridges between the two fields, resulting in Arabic linguistic research that is both original and modern at the same time.